KOMITE AUDIT DAN AUDIT REPORT DELAY: STUDI EMPIRIS PERUSAHAAN ENERGI DI INDONESIA - Maulana Yusuf; Setianingtyas Honggowati (Center for Economic Studies Universitas Katolik Parahyangan, 2024)
The audit committee is one of the crucial parties in achieving financial reporting timeliness because it supervises and monitors internal parties in compiling financial reports, supervises and monitors external parties in the independent audit process, and mediating problems between internal and external parties. The purpose of this research is to provide empirical evidence that audit committees characteristics impact audit report delay, especially in energy sector public companies. Multiple regression analysis is used to test the hypothesis. Using unbalanced panel data with a sample of 252 firm-year observations from companies listed on the IDX in 2017–2021, the result find that the audit committee size has a positive effect on audit report delay, while the academic audit committee has a negative effect on audit report delay, while the accounting/financial expertise audit committee has no significant effect on the audit report delay. This research contributes by adding to the literature regarding the characteristics of audit committees and their relation to audit report delay.